E-001 Update on the PISTE trial (Pragmatic Ischaemic Stroke Thrombectomy Evaluation). (14th July 2013) - White, P; Muir, K; Ford, G; Brown, M; Clifton, A
Abstract : Background: The KEY current clinical question in acute stroke management is whether a treatment policy of modern intra-arterial thrombectomy (IAT) added to IV thrombolysis (IVT) improve clinical outcomes over IVT alone. If the answer is yes and it applies to most patients with large vessel occlusive stroke, then the implications for acute stroke care and health services are enormous. Methods: PISTE is a UK based prospective, randomised controlled multicentre parallel group trial (PROBE design) of adjunctive modern mechanical thrombectomy (stentrievers with use of conscious sedation where possible) compared with intravenous thrombolysis in patients with acute ischaemic stroke due to an occluded anterior circulation major intracranial vessel. Concealed allocation. Funded by grant from the Stroke Association with some support from industry. Angiographic secondary outcomes will be blinded to allocation and independently adjudicated. Results: This is a RCT in active recruitment phase but information on progress to date and aggregated cohort recruited will be presented. The pre-planned PRISMA compliant meta-analysis of ongoing European academic IAT trials will be outlined. Conclusion: Pragmatic treatment policy trials are essential in hyperacute stroke intervention and are feasible within acceptable timeframes. Disclosures: P. White: 1; C; Covidien, Codman, Microvention, Acandis. 2; C; Microvention, Codman. K. Muir: 1; C; Covidien, Codman, Acandis. G. Ford: None. M. Brown: None. A. Clifton: None.